PENGARUH PENDAPATAN ASLI DAERAH, TRANSFER PEMERINTAH PUSAT DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KALIMANTAN BARAT 2019-2024 - Oktaviani Putri; Nella Yantiana; Gita Desyana (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to determine how the influence of Regional Original Revenue, Transfers from the Central Government, and Capital Expenditures on the financial performance of local governments in 14 districts / cities in West Kalimantan Province during 2019-2024. Regional financial performance is measured using the independence ratio. The background of this study is the importance of good regional financial management to support the success of regional autonomy. The method used is a quantitative approach with multiple linear regression analysis using SPSS software version 26. The data used is secondary data from the APBD realization report taken from the official website of the Directorate General of Fiscal Balance. The results showed that Regional Original Revenue had a positive and significant effect on regional financial performance. Transfers from the Central Government have a negative but significant effect, while Capital Expenditure has a positive but insignificant effect. Simultaneously, the three variables have a significant effect on regional financial performance. These findings indicate the importance of increasing own-source revenues and managing transfer funds efficiently to improve regional financial performance. Keywords : Regional Original Revenue, Transfers from the Central Gover, Capital Expenditures, Financial Performance of Local Governments